HOUSING CONDITION IN CORAL BARRACKS, NIGERIA - Milala, Sani Inusa; Maiyaki, Sani Aududu; Ishiyaku, Bala; Yayajo, Sakina; Idris, Ibrahim; Saad, Mustapha Umar (Journal of Environmental Science and Sustainable Development, 2021)
Housing conditions in the coral barracks become interesting as research subjects to find out that the housing condition covers all-encompassing in both the dwelling’s physical attributes and housing satisfaction. Generally, having satisfactory housing accommodation is among the most prized aspects of human begins’ lives and a key component of people’s material living standards. The aim of this study was to assess the attributes and level of housing conditions in Coral Barracks, Nigeria to explore housing conditions and their attributes and cover only the non-commissioned officers’ quarters. A quantitative method using a questionnaire survey was used and the population size was 774 apartments with a sample size of 260, while the data were analyzed using descriptive statistics as well as parametric measurements. A total number of 194 questionnaires retrieved from the respondents were used in the analyses. The findings from the physical condition attributes showed that the number of bedrooms, walls, and floors were in fair condition, while the roof, kitchen, and toilet/bath were in poor condition. Neighborhood attributes of hospitals, worship centers, sports facilities, and schools were in fair condition, building services attributes of security, water supply, fire protection, sewage & solid waste disposal and road networks were in fair condition, while laundry, internet, and drainage are in poor condition. The study recommends that a standard strategic plan for efficient barrack housing construction, management, and maintenance be designed. Dealing with the study, it can be concluded that housing conditions in coral barracks, Nigeria, are in the condition that requires rehabilitation to revitalize the standard of the housing condition implied that the management of Coral Barracks through the Logistics Department and Engineering Maintenance Group (EMG) is requested to expeditiously carry out general renovation of the soldiers’ accommodation as well as improve on the provision of auxiliary building services and neighbourhoods amenities in the study area with this it may still be part of the conclusion that the housing condition in the study is not fair.